2008
DOI: 10.1053/j.gastro.2008.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Pyloric Sphincter Dysfunction in nNOS−/− and W/Wv Mutant Mice: Animal Models of Gastroparesis and Duodenogastric Reflux

Abstract: Background and & Aims-Nitrergic nerves and interstitial cells of Cajal (ICC) have been implicated in the regulation of pyloric motility. The purpose of these studies was to define their roles in pyloric function in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 32 publications
4
55
0
1
Order By: Relevance
“…Unexpectedly, ICC depletion showed no effect on both components of the IJP, whereas disruption of NO/CO signalling in ICC by Prkg1 deletion blocks selectively the NO/COdependent sIJP. These findings are in line with data from mice lacking intramuscular ICC (W/W v mice) or the gene encoding nNOS 29,30 . The lower oesophageal sphincter and the pyloric sphincter are hypotensive, with normal nitrergic relaxation in W/W v mice due to the selective lack of excitatory cholinergic input from enteric neurons (loss of EJP, unaffected IJP, for comparison see Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Unexpectedly, ICC depletion showed no effect on both components of the IJP, whereas disruption of NO/CO signalling in ICC by Prkg1 deletion blocks selectively the NO/COdependent sIJP. These findings are in line with data from mice lacking intramuscular ICC (W/W v mice) or the gene encoding nNOS 29,30 . The lower oesophageal sphincter and the pyloric sphincter are hypotensive, with normal nitrergic relaxation in W/W v mice due to the selective lack of excitatory cholinergic input from enteric neurons (loss of EJP, unaffected IJP, for comparison see Fig.…”
Section: Discussionsupporting
confidence: 90%
“…These data provide the first genetic in vivo evidence for an essential role of ICC in excitatory neurotransmission to smooth muscle cells in acute ICC-depleted adult animals and support findings in W/W v germline mutant mice that display reduced excitatory neurotransmission and a hypotensive lower oesophageal and pyloric sphincter 12,13,16,29,30 .…”
Section: Icc Depletion Blocks Excitatory Enteric Neurotransmissionsupporting
confidence: 81%
See 1 more Smart Citation
“…Neuronal nitric oxide synthase-deficient (nNOS −/− ) mice and diabetic animals (eg, Streptozotocin treated rats, nonobese diabetic [NOD] mice, and ob/ob mouse model of obesity) are well-known animal models of GP. [19][20][21][22] The results observed in ICC deficient mice or rats were contradictory. They have been used both as a model of duodenogastric reflux based on the presence of a hypotensive pyloric sphincter, as well as delayed gastric emptying mimicking GP.…”
Section: Gastroparesis and Interstitial Cells Of Cajal In Animal Modelsmentioning
confidence: 99%
“…They have been used both as a model of duodenogastric reflux based on the presence of a hypotensive pyloric sphincter, as well as delayed gastric emptying mimicking GP. 19,23 Ultrastructural changes of ICC as well as ICC depletion have been observed in diabetic animal models. Two recent studies by Chen et al 24,25 showed that diabetes induced by streptozotocin in rats delays gastric emptying, decreases contractions of the antral strips, and decreases ICC-IM, ICC-MP, and ICC-SM counts in the antrum.…”
Section: Gastroparesis and Interstitial Cells Of Cajal In Animal Modelsmentioning
confidence: 99%